Análise de Variáveis Contábeis para Implementação de empresa de Reaproveitamento de Resíduos de Gesso Pernambuco. - Silva, Maristela Maria Moura (2018)
The high growth that occurred in the field of construction and mining currently in the Brazilian states, has caused a new problem that is illegal disposal and the lack of a solid waste management of demolition, with gypsum being one of the most used inputs by civil construction, And of the minerals most used in Brazil, both by industry and agriculture, in recent years, which during its application process results in polluting waste, harmful to the environment, have brought numerous problems for society, among which the following stand out: Proliferation of vectors of diseases such as dengue, obstruction of slopes causing rainfall, irregular occupation of public lands by the needy population, with risks of collapse, among others. The recycling of materials obtained by the disposal of solid wastes in specific gypsum can be reused in several ways, one of these in agriculture, gypsum has the primary function of lowering the toxicity of a very present element in tropical soils, aluminum (Al 3+) . In the application of gypsum, when it reacts with water, calcium (Ca2 +) separates from sulphate (SO42-). The latter reacts with the aluminum, neutralizing it. With the toxicity of aluminum, thus prevented the low productivity of the soil. The objective of this work was to analyze economically the implementation for a company of reuse of gypsum waste in the state of Pernambuco. The methods used are the economic viability that has cost estimates to verify the profit and the unit cost of the reuse process. The NPV of R $ 112,562.03 with a return of 4.75 years of investment with 18% for amortization of the investment. The internal rate of return for analysts was 65% in the project rate being a good result, being above the average of 9%, in the investment of R $ 732,751.14. As a result, there was a dynamic system and the economic feasibility that fits the realities of cooperatives and municipalities of small and medium size that have passed a renewable material that can requalify their soils in an economical and sustainable way.